Harnessing Wharton's jelly stem cell differentiation into bone-like nodule on calcium phosphate substrate without osteoinductive factors. (February 2017) - Mechiche Alami, S.; Rammal, H.; Boulagnon-Rombi, C.; Velard, F.; Lazar, F.; Drevet, R.; Laurent Maquin, D.; Gangloff, S.C.; Hemmerlé, J.; Voegel, J.C.; Francius, G.; Schaaf, P.; et al.
Graphical abstract: Bone regenerative medicine. Abstract: An important aim of bone regenerative medicine is to design biomaterials with controlled chemical and topographical features to guide stem cell fate towards osteoblasts without addition of specific osteogenic factors. Herein, we find that sprayed bioactive and biocompatible calcium phosphate substrates (CaP) with controlled topography induce, in a well-orchestrated manner, Wharton's jelly stem cells (WJ-SCs) differentiation into osteoblastic lineage without any osteogenic supplements. The resulting WJ-SCs commitment exhibits features of native bone, through the formation of three-dimensional bone- like nodule with osteocyte-like cells embedded into a mineralized type I collagen. To our knowledge, these results present the first observation of a whole differentiation process from stem cell to osteocytes-like on a synthetic material. This suggests a great potential of sprayed CaP and WJ-SCs in bone tissue engineering. These unique features may facilitate the transition from bench to bedside and the development of successful engineered bone. Statement of Significance: Designing materials to direct stem cell fate has a relevant impact on stem cell biology and provides insights facilitating their clinical application in regenerative medicine. Inspired by natural bone compositions, a friendly automated spray-assisted system was used to build calcium phosphate substrate (CaP). Sprayed biomimetic solutions using mild conditions led to the formation of CaP with controlled physical properties, good bioactivity and biocompatibility. Herein, we show that via optimization of physical properties, CaP substrate induce osteogenic differentiation of Wharton's jelly stem cells (WJ-SCs) without adding osteogenic supplement factors. These results suggest a great potential of sprayed CaP and WJ-SCs in bone tissue engineering and may facilitate the transition from bench to beside and the development of clinically successful engineered bone.